Psychological Well-being and its Relationship with the Academic Achievement of Lithuanian Students - Rapuano, Violeta (Socialiniai tyrimai, 2019)
The present article aims to analyze the role of psychological well-being when predicting Lithuanian students’ academic achievement. The study was conducted using the quantitative method of questionnaire survey. Data of the survey were analyzed using correlation and multiple regression analyses. It was found that psychological well-being and all its dimensions had a significant positive relationship with academic achievement. Furthermore, such dimensions of psychological well-being as environmental mastery and self-acceptance were found to be significant predictors of students’ academic achievement.
Keywords: psychological well-being; academic achievement; students